2004
DOI: 10.1063/1.1738101
|View full text |Cite
|
Sign up to set email alerts
|

Broadening and line mixing in the 20 0←01 10, 11 10←00  and 12 20←01 1 Q branches of carbon dioxide: Experimental results and energy-corrected sudden modeling

Abstract: Using both a difference frequency spectrometer and a Fourier transform spectrometer, we have measured transitions in the 12 (2)0<--01 (1)0 band of carbon dioxide at room temperature and pressures up to 19 atm. The low-pressure spectra were analyzed using a variety of standard spectral profiles, all with an asymmetric component to account for weak line mixing. For this band, we have been able to retrieve experimental line strengths and the broadening and weak mixing parameters. In this paper we also compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…We find the room temperature parameters to be: A = 0.0182 cm À1 /atm, k = 0.7396, b = 0.06, and d c = 6.0 Å , very close to the values reported in Ref. [52].…”
Section: Energy Corrected Sudden Calculations For Rotational Transfersupporting
confidence: 88%
See 3 more Smart Citations
“…We find the room temperature parameters to be: A = 0.0182 cm À1 /atm, k = 0.7396, b = 0.06, and d c = 6.0 Å , very close to the values reported in Ref. [52].…”
Section: Energy Corrected Sudden Calculations For Rotational Transfersupporting
confidence: 88%
“…The basic rates are expressed through an exponential power law dependence [51][52][53] QðJ where E J is the rotational energy of level J. This type of scaling law is often referred to as the ECS-EP model that depends on the d c , A, k, and b parameters of the ECS-EP model.…”
Section: Energy Corrected Sudden Calculations For Rotational Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…The Energy Corrected Sudden fitting law is an extension of the Infinite-Order Sudden law (IOS) [38] for cases where molecular collisions are not 'sudden' anymore [38,[40][41][42][43][44]. Many instances have shown that this is true for molecular collisions and consequently that the isolated lines are not Lorentzian at their wings (yet this deviation does not affect the width of the spectral line).…”
Section: Energy Corrected Sudden Calculations For Rotational Transfermentioning
confidence: 99%